A study on the characteristics of potential landfill site in Kuantan, Pahang, Malaysia - Nurlina Auni , Mazelan (2012)
Most countries give full attention to the selection of new waste disposal sites. When the current waste disposal sites are met, searching for a new landfill site will be a complicated process and takes a long time. Site selection is crucial and necessary for waste management in areas where are growing rapidly. Due to the complexity of waste management systems choose a new landfill as appropriate, a number of alternatives and evaluation criteria required for consideration. A study was carried out in the Kuantan to overcome the problem of waste disposal sites in Jabor, Kuantan has become critical. The main purpose of this study was to identify potential new disposal site in Kuantan, Pahang. Besides, this study was to determine the evaluation criteria which important for waste disposal sites and it will be used in the Analysis Hierarchy Process (AHP) for the selection of disposal sites. In an effort to make the right decision in assessing the important evaluation criteria, a questionnaire was designed and distributed to the experts. The data obtained from the questionnaires will be analyzed using the Statistical Package for Social Sciences (SPSS). The results from this study, the alternatives and the important criterion in the selection of disposal sites can be used for further study by using Analysis Hierarchy Process (Al-IP). Based on the results, four main criteria which important in the selection of a suitable waste disposal sites are hydrological and hydrogeo logical, morphologic, social factors and economic impact.